β-glucan mimics tissue damage signaling and generates a trade-off between head kidney and spleen to activate acquired immunity in vaccinated tilapia (Oreochromis niloticus) - Reis, Ingrid Camargo dos [UNESP]; Fierro-Castro, Camino; Gonçalves, Giovanni Sampaio; Moromizato, Basia Schlichting [UNESP]; Tort, Lluis; Biller, Jaqueline Dalbello [UNESP] (Elsevier, 2021)
The association of vaccines with immunostimulants such as β-glucan, promote the production of cytokines, competent immune cells and antibodies. However, differences between β-glucan types and trials make it difficult to understand β-glucan's mechanism of action. In this study, three trials were carried out with control and fish fed β-glucan, the first trial occurred at 15 days; the second trial occurred at 30 days when we associated β-glucan and vaccine; and the third trial occurred at 15 days post-challenge with Streptococcus agalactiae in tilapia (O. niloticus) in order to investigate immune-related gene expression in the head kidney and spleen using real-time qPCR. We found increases in HSP70, IL-6, IL-1β, TNF-α, IL-10, Lys and C3 predominantly in the head kidney, except for IgM expression, which prevailed in the spleen, under vaccinated + β-glucan action. This demonstrates the trade-off presented by the head kidney and spleen after immunostimulation in order to produce acquired immunity, as well as an increase in HSP70 expression in vaccinated + β-glucan fish. The results suggest that β-glucan stimulates the immune response through damage-associated molecular patterns (DAMPs) recognition. Therefore, these dynamics of the immune response promote a more robust defense against disease.
Keywords: Damage-associated molecular patterns (DAMP); Immune-related gene; Immunology; Immunostimulant; Lymphoid organ; Streptococcus agalactiae